ANALYSIS OF THE INFLUENCE OF PER CAPITA INCOME, EDUCATION LEVEL, POPULATION OF PRODUCTIVE AGE, AND HUMAN DEVELOPMENT INDEX ON POVERTY IN INDONESIAN PROVINCES - Amanda Putri Salsabila; Amanda Afriza Putri; Amalia Nasution; Radja Janna Lubis; Umi Hasanah; Rita Handayani (PT. Arsil Reka Engineering, 2024)
This study aims to analyze the influence of per capita income, education level, the productive-age population, and the human development index on poverty levels in Indonesian provinces. The data used in this study are secondary data obtained from the Indonesian Central Bureau of Statistics and the World Bank. The analysis method used is multiple linear regression. The results of the study show that per capita income, education level, and the human development index have a significant influence on poverty levels in Indonesian provinces. However, the number of productive-age population does not have a significant influence on poverty. These findings have important policy implications in efforts to reduce poverty levels in Indonesian provinces.